Validity and Usefulness of Revised WHO Guidelines in Children with Dengue Fever - Sriram Pothapregada (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Dengue fever is the most rapidly spreading mosquito borne viral infection with a 30-fold increase in the disease burden over last five decades with a variable clinical course and outcome. The World Health Organization (WHO) published treatment guidelines in 1997 and further revised in 2009 to facilitate early diagnosis and intervention in severe cases. Aim: To evaluate the validity and usefulness of Revised 2009 WHO guidelines in comparison to 1997 guidelines in children with dengue fever. Materials and Methods: All children (0-12 yrs of age) diagnosed and confirmed as dengue fever admitted at a tertiary care hospital in Puducherry from 1st August 2012 to 31st December 2015 were reviewed retrospectively from hospital case records. All children were classified as per the 1997 and 2009 Revised WHO guidelines for dengue fever. Results: Out of 434 children admitted with dengue fever the diagnosis was confirmed in 294 cases (67.7%). The mean age of presentation was 7.0(3.3) years. M:F ratio was 1.1:1. As per 1997 WHO guidelines the cases were classified as dengue fever 246(83.7%), dengue haemorrhagic fever 22(7.5%) and dengue shock syndrome 26(8.6%). As per WHO 2009 guidelines they were classified as dengue without warning signs 42(14.3%), dengue with warning signs 215(73.1%), and severe dengue 37(12.6%). Dengue fever requiring early intervention as per 1997 and 2009 WHO guidelines were seen in 96(27.2%) and 153 cases(52%) respectively. The most common manifestation of severe dengue infection was shock (40.1%), bleeding (20.4%) and multiorgan failure (2.0%). Conclusion: The revised WHO 2009 dengue fever guidelines classified more cases requiring early and timely intervention but remained to be too broad and non-specific in terms of pathophysiology, fluid management and use of blood products. Our experience recommends a need for further modifications in the guidelines especially with changing epidemic pattern of presentation.